Regulation of LRRK2 promoter activity and gene expression by Sp1. Issue 1 (December 2016) - Wang, Juelu; Song, Weihong
Abstract Background The dopaminergic neurodegeneration in the nigrostriatal pathway is a prominent neuropathological feature of Parkinson's disease (PD). Mutations in various genes have been linked to familial PD, and leucine-rich repeat kinase 2 (LRRK2) gene is one of them. LRRK2 is a large complex protein, belonging to the ROCO family of proteins. Recent studies suggest that the level of LRRK2 protein is one of the contributing factors to PD pathogenesis. However, it remains elusive how LRRK2 is regulated at the transcriptional and translational level. Results In this study, we cloned a 1738 bp 5'-flanking region of the human LRRK2 gene. The transcriptional start site (TSS) was located to 135 bp upstream of translational start site and the fragment −118 to +133 bp had the minimum promoter activity required for transcription. There were two functional Sp1- responsive elements on the human LRRK2 gene promoter revealed by electrophoretic mobility shift assay (EMSA). Sp1 overexpression promoted LRRK2 transcription and translation in the cellular model. On the contrary, application of mithramycin A inhibited LRRK2 transcriptional and translational activities. Conclusion This is the first study indicating that Sp1 signaling plays an important role in the regulation of human LRRK2 gene expression. It suggests that controlling LRRK2 level by manipulating Sp1 signaling may be beneficial to attenuate PD-related neuropathology.